Participatory Communication Strategies of Administrators at Suan Dusit University - Laksanayothin, Pattama; Boonprawes, Supasiri; Skunhom, Venus; Tungdamnernsawad, Supaporn (Mahachula Academic Journal, 2026)
This research aimed to examine participatory communication strategies of administrators at Suan Dusit University. A qualitative research methodology was employed through in-depth interviews with senior administrators, including the President, Vice Presidents, Deans, and Directors of Offices. Data were analyzed using content analysis. The findings revealed that: 1) The university developed participatory communication strategies through decentralization and empowerment, allowing Vice Presidents to make direct decisions within their respective areas of responsibility, while developing diverse communication channels appropriate for each target group, with informal channels demonstrating high effectiveness; 2) Mindset emerged as the most critical factor for collaborative communication, shared ownership creation, and open-mindedness toward diverse perspectives; organizational culture rooted in the Home Economics School tradition fostered family atmosphere and bonding, though seniority culture resulted in personnel being more receptive than expressive; 3) The university’s strengths included family culture, clear structure, and high flexibility, while weaknesses comprised personnel reluctance to express opinions and delayed processes in certain stages; 4) The main challenges were changing personnel mindset, hierarchical culture, and reluctance to engage in constructive criticism; and 5) Administrators played roles as role models, demonstrated openness to listening, and conducted field visits to understand actual problems, alongside continuous evaluation both quantitatively and qualitatively.